Anetoderma in a child with systemic lupus erythematosus. - Açarı, C.; Torun Bayram, M.; Özmen, D.; Soylu, A.; Özbahçıvan, Ö.; Özer, E.; Kavukçu, S. (European Journal of Pediatric Dermatology, 2020)
Anetoderma is a rare cutaneous disorder characterized by the loss of normal elastic tissue, clinically manifested as atrophic patches in the body and extremities. Immunological mechanisms may play a role in this process. Here, we report an 11-year-old boy with systemic lupus erythematosus who presented with numerous well-circumscribed atrophic lesions on the trunk and limbs. Histopathological examination showed that elastic fibers were sparse in the superficial dermis and almost completely absent in the mid dermis. This finding was consistent with anetoderma. There were not antiphospholipid antibodies, but D-dimer level was high. We think that anetoderma originated from a developing microthrombosis process, especially as supported by the increased D-dimer.